Perubahan Pengetahuan Risiko LBP Sebelum dan Sesudah Penyuluhan pada Kelompok Wanita Tani Ngori - Nabylla Sharfina Sekar nurriwanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Low Back Pain (LBP) is a common musculoskeletal disorder, particularly prevalent among workers in the informal sector. The group of women farmers engaged in bamboo weaving in Dusun Ngori is considered at high risk of experiencing LBP, primarily due to a lack of understanding about ergonomic working positions during daily activities. This study aims to determine the difference in knowledge regarding LBP risk before and after a health education intervention. The research employed a pre-experimental design with a one-group pretest-posttest approach. A total of 24 respondents from the bamboo weaving women's farmer group in Dusun Ngori participated in the study. Data were collected using a questionnaire administered before and after the educational intervention. The Wilcoxon Signed-Rank Test was used to analyze the significance of changes in knowledge levels. The results showed a significant increase in knowledge following the health education session. These findings indicate that health education has a positive impact on increasing awareness and understanding of LBP risk. Therefore, it is recommended that the local public health center conduct regular monitoring and continue educational programs to prevent LBP, especially among informal sector workers such as this group of women farmers. Ongoing health promotion using participatory and community-based approaches is considered effective in reducing health risks associated with non-ergonomic working positions.